Limit-feeding a high-concentrate diet may alter nutrient absorption - J.O. Wallace; W.F. Miller; B.J. Johnson; Christopher D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2007)
Feeding newly arrived cattle is commonly characterized by a few days of feeding longstemmed hay followed by a series of step-up diets, wherein concentrate levels are increased to promote ruminal adaptation to a highconcentrate finishing diet. This is done to give the rumen microbes time to adjust to larger amounts of readily fermentable starches in cereal grains. Rumen epithelial adaptation may be achievable by limit-feeding a finishing diet, with gradual increases in feed intake, until the cattle are on full feed. If this can be achieved without causing ruminal disorders and days off feed, then the cost of feeding cattle can be reduced. By limit-feeding, the higher roughage step-up diets are replaced with a single high-concentrate diet. The cost of grain is less than that of roughage, and there are decreased costs in terms of storage space, waste disposal (due to decreased manure production), and mixing and hauling of rations. The purpose of this experiment was to examine the effects of a traditional step-up program versus a limit-fed finishing diet in terms of dry matter intake, acetate to propionate ratio, and ruminal dilution rate. Diet effects on volatile fatty acid concentration and absorption were also examined by using valerate as a marker for volatile fatty acid absorption.
Keywords: Cattlemen& #x27; s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; Nutrient absorption